2000
DOI: 10.1037/0022-006x.68.6.1102
|View full text |Cite
|
Sign up to set email alerts
|

The relation of religious belief and practices, depression, and hopelessness in persons with clinical depression.

Abstract: Religious belief and practices have been associated with lower levels of depression in persons dealing with stressful situations. In this study, researchers examined this relationship in 271 persons diagnosed with clinical depression. It was hypothesized that religious belief and practices would be associated with lower depression and that this relationship would be mediated by hopelessness. Religious belief, but not religious behavior, was a significant predictor of lower levels of hopelessness and depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(62 citation statements)
references
References 35 publications
3
58
1
Order By: Relevance
“…Pargament (1996) suggested that certain spiritual factors, such as religious coping methods, have been found to predict adjustment over and above the effects of non-religious coping. Ellison (1991) and others (Flaherty 1992;Lawson et al 1998;Murphy et al 2000;Ross 1990;Young et al 2000) found consistent indications in their studies that spirituality plays a vital role as a coping mechanism, against negative life events. Results from the path analysis suggest two things: first, that abuse had no direct effect on spirituality, and second, that spirituality had a direct impact on positive affect, but not on negative affect.…”
Section: Spirituality As a Therapeutic Resourcementioning
confidence: 67%
See 1 more Smart Citation
“…Pargament (1996) suggested that certain spiritual factors, such as religious coping methods, have been found to predict adjustment over and above the effects of non-religious coping. Ellison (1991) and others (Flaherty 1992;Lawson et al 1998;Murphy et al 2000;Ross 1990;Young et al 2000) found consistent indications in their studies that spirituality plays a vital role as a coping mechanism, against negative life events. Results from the path analysis suggest two things: first, that abuse had no direct effect on spirituality, and second, that spirituality had a direct impact on positive affect, but not on negative affect.…”
Section: Spirituality As a Therapeutic Resourcementioning
confidence: 67%
“…It could be speculated that beliefs that counter hopelessness, such as religious beliefs, form an important part in this equation. Murphy et al (2000) indicated such a pattern based on their findings that religious belief related to emotional well-being.…”
Section: Spirituality Religiosity and Child Abusementioning
confidence: 90%
“…Several of these strategies may be important to affect regulation and adjustment. For example, religious beliefs and use of religious thoughts (though not necessarily religious behavior) have been related to healthy adjustment (e.g., Koenig, George, & Siegler, 1988;Murphy et al, 2000; but see Carver & Scheier, 1994;Park & Cohen, 1993 for contrasting findings). In addition, mindfulness (including mindful observation) has long been viewed as an adaptive affect-regulation strategy within Eastern traditions and Western psychology alike (cf.…”
Section: Comparison To the Cerqmentioning
confidence: 96%
“…94 Murphy and colleagues investigated hopelessness with a similar intention of identifying it as a mediator. 95 They found that religious belief, as measured with the Religious Well-Being Scale, was negatively associated with hopelessness, as measured with the Beck Hopelessness Scale. Also, greater hopelessness predicted more depressive symptoms.…”
Section: Potential Mediators Of the Health Benefits Of Religiousnessmentioning
confidence: 99%